Successful Use of Salvage Bacteriophage Therapy for a Recalcitrant MRSA Knee and Hip Prosthetic Joint Infection - Jonathan Schoeffel; Elizabeth Wenqian Wang; Dustin Gill; Joseph Frackler; Bri'Anna Horne; Theodore Manson; James B. Doub (MDPI AG, 2022)
Prosthetic joint infections are a serious complication of joint replacement surgery due to the significant morbidity and financial burden that is associated with conventional treatments. When patients fail the gold standard two-stage revision surgery, very limited, well-defined standardized approaches are available. Herein, we discuss the case of a sixty-four-year-old woman who had a recalcitrant MRSA prosthetic joint infection of her knee and hip that failed repeated conventional surgical and medical treatments. Only after receiving intraoperative and intravenous bacteriophage therapy was the patient able to achieve cure of her prosthetic joint infections, as demonstrated by the lack of clinical recurrence and sterility of intraoperative cultures while off antibiotics. This case reinforces that bacteriophage therapy holds promise in the treatment of prosthetic joint infections and more specifically in complicated cases who have failed conventional surgical and medical interventions.